Effects of electroacupuncture on postoperative cognitive dysfunction and its underlying mechanisms: a literature review of rodent studies - Zhao, Wenbo; Zou, Wei (Frontiers in Aging Neuroscience, 2024)
With the aging of the population, the health of the elderly has become increasingly important. Postoperative cognitive dysfunction (POCD) is a common neurological complication in elderly patients following general anesthesia or surgery. It is characterized by cognitive decline that may persist for weeks, months, or even longer. Electroacupuncture (EA), a novel therapy that combines physical nerve stimulation with acupuncture treatment from traditional Chinese medicine, holds potential as a therapeutic intervention for preventing and treating POCD, particularly in elderly patients. Although the beneficial effects of EA on POCD have been explored in preclinical and clinical studies, the reliability of EA is limited by methodological shortcomings, and the underlying mechanisms remain largely unexplored. Therefore, we have synthesized existing evidence and proposed potential biological mechanisms underlying the effects of EA on neuroinflammation, oxidative stress, autophagy, the microbiota-gut-brain axis, and epigenetic modification. This review summarizes recent advances in EA and POCD, provides a theoretical foundation, explores potential molecular mechanisms for the prevention and treatment of POCD, and offers a basis for conducting relevant clinical trials.